A Comparative Study of Adult Learners’ Motivation for Learning English as a Foreign Language According to Their Instruction by Single or Multiple Instructors at Geos Language Centre, Thailand - Link, Simon William; Eamoraphan, Suwattana (Scholar: Human Sciences, 2021)
The purpose of this quantitative study was to compare adult learners’ motivation for learning English as a foreign language according to their instruction by either a single instructor or by multiple instructors over a period of six weeks at Geos Language Centre in Bangkok, Thailand. The sample population of this study consisted of 67 adult-learner students enrolled in private English as a foreign language courses during the period of April to July 2020. These students comprised two groups under investigation during the period of this study: 1) Those who received instruction from a single instructor, and 2) Those who received instruction from multiple instructors. The Questionnaire for Measuring Motivation for Learning English as a Foreign Language (QMMLEFL), adapted from the Attitude / Motivation Test Battery (AMTB) by Gardner (2004), was used to measure the level of adult learners’ motivation for learning English as a foreign language (EFL). Descriptive statistics (means and standard deviations) were calculated, and statistical hypothesis testing (comparative analysis using paired samples t-tests and an independent samples t-test) was performed from data collected to pursue the research objectives and accept or reject the research hypotheses of this study. The research findings did not indicate that there was a statistically significant difference in the gain in motivation for learning English as a foreign language over a six-week period of study between adult learners who studied with a single instructor and adult learners who studied with multiple instructors. Recommendations for adult learners and instructors of English as a foreign language and language institute administrators and future researchers are provided.